(untitled) (Bisanzio e l’Occidente, 2018)
Saint Theodosia of Caesarea, martyred during the Diocletianic persecution, was venerated in the Byzantine Empire, notably in Constantinople. Eusebius of Caesarea’s De martyribus Palaestinae (BHG 1775) is the source of all the Greek hagiographic accounts of her martyrium, one of which, nowadays lost, was translated in Latin between the 5th and the 7th century (BHL 8090). Another independent translation of the lost Greek Passio was performed in Venice in the last centuries of the Middle Ages. According to Francesco Negri’s Historia Theodosiae and to the anonymous Martyrium sanctae Theosiae - an incunabulum printed by Antonio Zanchi in 1498 - in the first half of the 15th century the cult of Saint Theodosia was practiced and promoted in Venice in at least in two churches, San Tomà, and Corpus Domini. The ‘Venetian’ Passio is solely witnessed by the ms. Milano, Biblioteca Braidense, Gerli 26 and it has never been printed. The aim of this paper is to publish a critical edition of the text and to understand the historical circumstances under which it was elaborated.